Observing Ion Motion in Conjugated Polyelectrolytes with Kelvin Probe Force Microscopy. (20th February 2017) - Collins, Samuel D.; Mikhnenko, Oleksandr V.; Nguyen, Thanh Luan; Rengert, Zachary D.; Bazan, Guillermo C.; Woo, Han Young; Nguyen, Thuc‐Quyen
Abstract : Conjugated polyelectrolytes (CPEs) are polymer semiconductors whose properties are affected by the presence of covalently fixed and mobile ions. These structural components lead to interfacial dipoles, electrochemical doping, and mixed ionic and electronic conductivity. While the behavior of ionic carriers is important to a number of CPE applications, it remains difficult to quantify ion transport in films due to interference from electronic carriers; relationships between molecular structure and ion conductivity are thus not well understood. This work demonstrates direct observation of ions in six different CPE films using Kelvin probe force microscopy. Surface potential measurements of thin, planar CPE device structures are used to map the distribution of ions through the simple electrostatic relationship between potential and charge density. The transport of mobile ions within the CPE bulk can be studied through the time‐dependent relaxation of bias‐stressed CPE films, through which the decay of ion populations near each electrode is measured and carefully modeled, leading to estimated values of ionic mobility and effective ionic carrier density. The results show that ion transport is most strongly impacted by the number of ion‐bearing side chains per monomer, which facilitate room temperature ion transport via vibrational motion. Abstract : A method for directly observing and quantifying the transport of mobile ions in conjugated polyelectrolytes (CPEs) is presented. The relaxation of mobile ions within bias‐stressed CPE films is measured with Kelvin probe force microscopy and modeled using drift‐diffusion Monte Carlo simulations of ion hopping. This approach is used to obtain new insights into relationships between CPE structure and ion transport.